Profile of Junior High School Students' Creative Thinking Ability and Numerical Literacy in Solving Mathematical Problems - Nasruddin Nasruddin; Jahring Jahring (IKIP Mataram, 2024)
This study aimed to describe the profile of creative thinking abilities and mathematical numeracy literacy of junior high school students in solving mathematical problems. Students' creative thinking abilities in this study refer to aspects of fluency, flexibility, originality, and elaboration. Meanwhile, students' mathematical numeracy literacy refers to indicators of formulating problems systematically, reasoning, and solving problems. This type of research is qualitative descriptive research. The subjects of this study were class VIII students of SMP Negeri 1 Latambaga. The research instrument used was non-routine test questions given to students, and data processing was carried out qualitatively. The results showed that descriptively, the students' mathematical creative thinking abilities were in the quite creative category, whereas 40 students were in the quite creative category with an average score of 51.43. Meanwhile, from the numeracy literacy data, students are in the good category, where students who are in the good category are 40 students with an average score of 63.47. Based on these data, it can be concluded that students' mathematical numeracy literacy skills are more likely than the mathematical creative thinking abilities of class VIII students of SMP Negeri 1 Latambaga.